Subject-based lesson study supporting Merdeka Curriculum enactment: Findings from Malang City science teachers - S. Saparuddin; I. Istiqomah; Herawati Susilo; I. Ibrohim; Adisti Ratnapuri (Journal of Community Service and Empowerment, 2024)
Developing teacher capability in implementing the Merdeka curriculum can take advantage of the activity of sustainable lesson study. Lesson study conducted at the subject teacher community provides a place for teachers to learn collaboratively to improve their professionalism. This study aims at present the findings of the implementation of a subject-based lesson study carried out among junior high school science teachers in Malang City, Indonesia, and expose their responses regarding the impact of this activity on their professional development in supporting the Merdeka Curriculum enactment. Teachers are actively involved and enthusiastic in participating in lesson study activities. The teacher stated that the implementation of subject-based lesson study was a forum for mutual learning and improving teaching skills so that it supported the implementation of the Merdeka Curriculum. Even so, continuous implementation accompanied by strengthening the principles of lesson study and learning principles that emphasize student involvement as well as developing students' thinking skills is needed. Finally, the constraints and expectations expressed by the teacher can be considered for designing a subject-based lesson study implementation model to form sustainable lesson study for learning communities in the future.